O Ensino da Matemática Financeira como Possibilidade de Refletir sobre Educação Financeira via Resolução de Problemas - Marconato, Eliane do Carmo (2020)
One of the deficiencies perceived both in school education and in the family environment is in Financial Education and the lack of basic knowledge of Financial Mathematics, which lead many families to make wrong decisions in relation to finance, generating problems that negatively impact the quality of life of students and their families. Thus, the theme of this study is Financial Education and the teaching of Financial Mathematics, which aims to answer the following question: What impacts can be favored in the education of the student when Financial Education is aimed at from concepts of Financial Mathematics in association with the Problem solving? The main objective of this study is to analyze the reflections produced by students when submitted to the educational context fostered by Financial Education, combined with Financial Mathematics and Problem Solving. The theoretical framework that supported this study was Financial Education, Cerbasi (2019), Kiyosaki (2017), Carrilho (2012), Melo (2016), Auebe (2013), Hill (2009), Vieira (2015) and Eker (2006) ) and the Problem Resolution Methodology in Onuchic (2011). The collected data were analyzed following the steps proposed by Bogdan and Biklen (1994), an inductive analysis and the triangulation between the collected data, the theoretical framework and the researcher's analysis. From the data, five categories emerged that impact on student education: self-knowledge, financial planning, creation of healthy habits, family dialogue and the learning of financial concepts.